Autogenous bone graft in conjunction with enamel matrix derivative in the treatment of deep periodontal intra-osseous defects: a report of 13 consecutively treated patients - Leonardo Trombelli (Blackwell Synergy, 2006)
Aim: The purpose of the present study was to investigate the effectiveness of a regenerative procedure based on supra-crestal soft tissue preservation in association with combined autogenous bone (AB) graft/enamel matrix derivative (EMD) application in the treatment of deep periodontal intra-osseous defects. Methods: Thirteen consecutively treated patients, seven females and six males, aged 30–65 years, three smokers, were included. A total of 15 deep, one- to two-wall intraosseous defects were selected. Immediately before surgery and 6 months after surgery, pocket probing depth (PPD), clinical attachment level (CAL), and gingival recession (REC) were recorded. Results: PPD amounted to 9.4 1.8mm before surgery, and decreased to 4.7 1.2mm post-surgery (po0.0000). CAL varied from 10.5 2.0mm pre-surgery to 6.2 1.7mm post-surgery (po0.0000), with CAL gain averaging 4.3 1.4 mm. Fourteen (93.3%) defects presented CAL gain X3 mm. REC change was 0.4 0.7 mm. Conclusions: Results from the present study indicated that a regenerative procedure based on supra-crestal soft tissue preservation and combined AB/EMD treatment leads to a clinically and statistically significant improvement of soft tissue conditions of deep periodontal intra-osseous defects.